BELAJAR AGAMA ISLAM DI KAMPUS UNIVERSITAS HALUOLEO KENDARI (Relevansi dan Ketepatannya Modul Bahan Ajar dengan Kebutuhan dalam Perspektif Tadqiq) - Syarifuddin Syarifuddin (Balai Penelitian dan Pengembangan Agama Makassar, 2018)
The subject of religious education is one of the general courses that must beprogrammed by students in public universities with the aim that students canhave a religious spirit of faith and fear the Almighty God in carrying out theprofession, not to become a religious expert. Based on these objectives, thematerial should be taught according to the needs of students. In addition, thecampus should provide standard religious reading materials, can be used as ageneral reference by lecturers and students, and meet scientific standards thatmake it easy for readers. This study reviewed Islamic Religion textbooks inHaluoleo Kendari University based on relevance and accuracy with needs,using the approach and analysis of tadqiq. From the search results, the teachingmaterial used was made by the lecturer only limited to the teaching materialmodule. In this study, there are three modules that are used as study material,modules written by Bambang Sugianto, Muammal Gadafi and Jahadaa. Fromperspective of the discussion theme, the three modules appear to be differentfrom each other. But in general, it refers to the regulations issued by theDirectorate General of DIKTI Ministry of National Education and the DirectorGeneral of Religion Education Ministry of Religion. While from the perspectiveof the accuracy of the quotation from the Qur'anic verse, Hadith and generalquotations, the three modules are not consistent in writing techniques so that itcan be difficult for readers, especially those who work in non-religious fields